Brand Name Types and Consumer Demand: Evidence from China’s Automobile Market - Wu, Fang; Sun, Qi; Grewal, Rajdeep; Li, Shanjun (Journal of Marketing Research, 2019)
Brand naming challenges are more complex in logographic languages (e.g., Chinese), compared with phonographic languages (e.g., English) because the former languages feature looser correspondence between sound and meaning. With these two dimensions of sound and meaning, the authors propose a four-way categorization of brand name types for logographic languages: alphanumeric, phonetic, phonosemantic, or semantic. Using automobile sales data from China and a discrete choice model for differentiated products, the authors relate brand name types to demand, with evidence showing that Chinese consumers preferred vehicle models with semantic brand names (7.64% more sales than alphanumeric) but exhibited the least preference for phonosemantic names (4.92% lower sales than alphanumeric). Domestic Chinese firms benefited from semantic brand names, whereas foreign firms gained from using foreign-sounding brand names. Entry-level products performed better with semantic brand names, and high-end products excelled when they had foreign-sounding brand names. Thus, the four-way categorization of brand name types should help multinational firms and domestic Chinese firms understand and leverage the association between brand name types and consumer demand.